Implementation of Learning Plans Sharing and Jumping Tasks on Nominating Material for Inorganic Chemical Compounds to Grow Critical Thinking Skills - Eni Purwanti; Asep Supriatna; Sumar Hendayana; Umi Husnun Nihayah (Universitas Negeri Semarang, 2024)
This research aims to design and implement sharing and jumping task learning on inorganic compound nomenclature material to foster critical thinking skills. The applied didactical design research (Didactical Design Research) consists of 3 stages, namely: Didactical situation analysis before learning in the form of hypothetical didactical design including Didactical Pedagogical Anticipation (ADP), Metapedadidactical Analysis, and Retrospective Analysis after learning. The research subjects were 28 class X high school students. The research results found that: (1) The sharing and jumping task learning design on the nomenclature of inorganic compounds is quite effective in developing students' critical thinking skills. (2) Based on transcript analysis, most students can develop critical thinking skills, especially asking and answering clarifying/challenging questions. However, students have difficulty developing critical thinking skills in making and assessing valuable assessments. The sharing and jumping task learning design developed can be used as an alternative design in the nomenclature of inorganic compounds.